A note on Riesz elements in C*-algebras - David Legg (International Journal of Mathematics and Mathematical Sciences)
It is known that every Riesz operator R on a Hilbert space can be written R=Q+C, where C is compact and both Q and CQ-QC are quasinilpotent. This result is extended to a general C*-algebra setting.